2023
DOI: 10.1021/acsaelm.2c01750
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Bixbyite-Structured δ-Ga2O3 Thin Films Using β-Fe2O3 Buffer Layers by Mist Chemical Vapor Deposition

Abstract: Gallium oxide (Ga 2 O 3 ) possesses five polymorphs: α, β, γ, κ (ε), and δ. Although the first four polymorphs have been well-studied, there are few reports on δ-Ga 2 O 3 . Here, we demonstrate the epitaxial growth of metastable δ-Ga 2 O 3 thin films by mist chemical vapor deposition using β-Fe 2 O 3 buffer layers. X-ray diffraction (XRD) 2θ−ω scan pattern revealed that (004) κ-Ga 2 O 3 grew on (111) yttria-stabilized zirconia (YSZ) without a buffer layer or with a bcc-In 2 O 3 buffer layer, whereas (222) δ-Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 42 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…Recently, our group successfully grew δ-Ga 2 O 3 thin films using a β-Fe 2 O 3 buffer layer with the same bixbyite structure grown on yttria-stabilized zirconia (YSZ) and reported that the experimental lattice constant of δ-Ga 2 O 3 was a = 9.255 Å, and its bandgap was %4.9 eV. [25] Without the buffer layers, the Ga 2 O 3 thin films exhibit a κ-phase on bcc-In 2 O 3 and YSZ. [26,27] Thus, β-Fe 2 O 3 possessing a small lattice mismatch with δ-Ga 2 O 3 (%1.6%) plays an important role in the growth of δ-Ga 2 O 3 thin films.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group successfully grew δ-Ga 2 O 3 thin films using a β-Fe 2 O 3 buffer layer with the same bixbyite structure grown on yttria-stabilized zirconia (YSZ) and reported that the experimental lattice constant of δ-Ga 2 O 3 was a = 9.255 Å, and its bandgap was %4.9 eV. [25] Without the buffer layers, the Ga 2 O 3 thin films exhibit a κ-phase on bcc-In 2 O 3 and YSZ. [26,27] Thus, β-Fe 2 O 3 possessing a small lattice mismatch with δ-Ga 2 O 3 (%1.6%) plays an important role in the growth of δ-Ga 2 O 3 thin films.…”
Section: Introductionmentioning
confidence: 99%